Emergent phenomena in computation: from enthropy to artificial consciousness? - Lumbreras Sancho, Sara (My University, 2025)
This talk will explore how computing provides a privileged window onto emergence—the phenomenon whereby novel, irreducible properties arise from simple interactions. We begin by clarifying key concepts: synergy, patterns, multi-level integration, phase transitions and the “edge of chaos.” Cellular-automaton experiments, from Conway’s Game of Life to Lenia, show that deterministic rules can yield unpredictable, self-organising structures, some even capable of universal computation. Linking state updates to thermodynamic entropy further reveals why complexity can flourish despite an overall trend toward disorder. Building on these foundations, we examine the startling emergent abilities of large language models (LLMs). When scaled, identical architectures suddenly display chain-of-thought reasoning, theory-of-mind inferences and even strategic deception—capabilities not explicitly programmed. Could subjective consciousness similarly emerge once computational systems cross a critical threshold? Competing accounts are surveyed: information-integration and global-workspace theories argue for substrate-independent consciousness, while proposals such as Orch-OR claim that physical quantum events remain indispensable. The ethical stakes are profound. If consciousness can arise in silicon, creating advanced AI may entail new moral subjects. Conversely, if human and machine cognition share a common computational basis, transhumanist projects aiming at deep integration or enhancement become plausible—and potentially perilous. Distinguishing between simulating and being conscious becomes central to policy and theology alike. Ultimately, emergent behaviour in software laboratories illuminates broader questions about life, mind and meaning. Recognising how complexity blossoms from humble rules urges humility about prediction, vigilance about unintended consequences and renewed dialogue between computer science, philosophy and faith.